Building 'blue': An eco-engineering framework for foreshore developments. (15th March 2017) - Mayer-Pinto, M.; Johnston, E.L.; Bugnot, A.B.; Glasby, T.M.; Airoldi, L.; Mitchell, A.; Dafforn, K.A.
Abstract: Urbanisation in terrestrial systems has driven architects, planners, ecologists and engineers to collaborate on the design and creation of more sustainable structures. Examples include the development of 'green infrastructure' and the introduction of wildlife corridors that mitigate urban stressors and provide positive ecological outcomes. In contrast, efforts to minimise the impacts of urban developments in marine environments have been far more restricted in their extent and scope, and have often overlooked the ecological role of the built environment as potential habitat. Urban foreshore developments, i.e. those built on the interface of intertidal and/or subtidal zones, have the potential to incorporate clear multi-functional outcomes, by supporting novel ecosystems. We present a step-by-step eco-engineering framework for 'building blue' that will allow coastal managers to facilitate planning and construction of sustainable foreshore developments. Adopting such an approach will incorporate ecological principles, thereby mitigating some of the environmental impacts, creating more resilient urban infrastructure and environments, and maximising benefits to the multiple stakeholders and users of marine urban waterfronts. Highlights: The addition of artificial structures to coastal systems have significant ecological impacts. In most foreshore developments, little effort is spend trying to maximise the potential environmental benefits. We introduce a framework as a guide so developments are built in ways to minimise impacts and maximise benefits. Clear ecological, quantitative targets must be defined before planning and development. Monitoring at all stages of eco-engineering activities is essential so outcomes can be evaluated against initial targets.